The impact of corrective exercises, kinesiology taping, and mechanical correction on pain and foot shape in women with hallux valgus - Jankowicz-Szymańska, Agnieszka; Wódka, Katarzyna; Smoła, Eliza; Bibro, Marta A. (Frontiers in Physiology, 2025)
BackgroundThis study aimed to assess the effect of corrective exercises and exercises supplemented by kinesiology taping or an orthosis on pain and foot alignment in women with hallux valgus (HV).MethodsEighty-two women with HV were randomly divided into groups: E (n = 24) who exercised for 12 weeks; EKT (n = 18) who exercised and used kinesiology taping on HV; EMC (n = 15) who performed exercise and used an orthosis to correct their big toe position; and CHV (25 women with HV without therapy). Additional control group C: (n = 31) women with normal hallux. The Wejsflog index, Clarke’s angle, alpha and beta angles, and pain intensity in the big toe area were assessed at the beginning and after therapy.ResultsThe Wejsflog index was significantly lower in women with HV and increased significantly after therapy in the E and EKT groups. Clarke’s angle did not differ between women with and without HV, and Clarke’s angle did not change after therapy. The HV angle decreased significantly in groups E and EKT but was still significantly greater than that in group C. The fifth toe varus angle did not differ between women with and without HV and decreased significantly in the right foot after therapy in group E. Pain in the HV area decreased significantly in all groups undergoing therapy.ConclusionWomen with HV have a greater forefoot width, but their longitudinal arch and fifth toe position do not differ. Exercises significantly reduce pain and improve hallux alignment. Combining exercises with kinesiology taping or an orthosis does not increase the therapeutic effect. Although the observed effects of conservative therapy are promising, it should be remembered that long-term effects have not been studied.Trial registrationThe Australian New Zealand Clinical Trials Registry (ACTRN12621000902897).